Fiscal theory of price level and coordination of monetary and fiscal policies: Understanding the current public debt and inflation dynamics - Mustapher, Marrium (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.